The Effect of Thymoquinone on Progressive Brain Damage: An Experimental Study in a Wistar Rat Model of Intracerebral Hemorrhage - Khamim Thohari; Asra Al Fauzi; Djoko Agus Purwanto (Borneo Journal of Pharmacy, 2026)
Background: ICH accounts for 20% of stroke cases, with a mortality rate of 40-50%. Despite available agents such as citicoline and piracetam, neuroprotective therapy for ICH remains unsatisfactory. TQ, the main active compound of Nigella sativa, has antioxidant and anti-inflammatory properties, but its role in ICH has not been studied. Objective: To evaluate the effect of thymoquinone on inhibiting the progression of brain damage in a Wistar rat model of ICH and to explore potential mechanisms Methods: Male Wistar rats (n=55, 200–220 g) were randomly assigned to five groups: control (no treatment), ICH without thymoquinone (terminated immediately), ICH with corn oil (terminated after 7 days), and ICH with thymoquinone at doses of 150 and 250 mg/kg body weight orally for 7 days (terminated after 7 days). ICH was induced by autologous blood injection (0.12 ml) into the brain parenchyma. Brain and serum samples were analyzed for NLRP3, TNF-α, IL-6, IL-1β, MMP-9, SOD, MDA, and necrotic cells using ELISA, immunohistochemistry, and histology. Statistical analyses included univariate analysis, Shapiro–Wilk, Kruskal–Wallis, and Mann–Whitney U tests. Results: TQ administration significantly altered MMP-9 levels (p=0.000), which increased compared with untreated ICH. TQ was associated with reductions in NLRP3, TNF-α, and IL-1β, while increasing SOD activityMDA levels remained elevated. These effects were dose-dependent, with the most consistent changes observed at 250 mg/kg. Conclusion: TQ modulated inflammatory and oxidative pathways in ICH and unexpectedly upregulated MMP-9, suggesting a dual role in early injury and later tissue remodeling. These findings support TQ as a potential natural neuroprotective agent.